Prarancangan Pabrik Ammonia Dari Hidrokarbon Dan Udara Dengan Proses KBR Dengan Disain Alat Utama CO2 Stripper - Emiliana Emiliana; Muhammad Iwan Fermi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The need for ammonia increases along with the number of finished products that use ammonia as a raw material in the manufacturing process. Ammonia is widely used in the fertilizer industry, textile industry and as a refrigerant. The main raw materials used in manufacture of ammonia by the KBR (Kellogg Braun and Root) process are natural gas and air. This plant is planned to operate for 330 days per year and work continuously for 24 hours/day with capacity of 350,000 ton/year which will be established in Dumai, Riau. The remaining time for 1 year of the operation process is used for shutdown, plant maintenance, maintenance and repair of equipment. The design of the main equipment in this plant is CO2 Stripper which functions to regenerate monodiethanolamine solvent by releasing carbon dioxide from monodiethanolamine solution. CO2 Stripper is operated at a pressure of 10 Bar and a temperature of 85 °C. The economic analysis on the design of this plant shows that the ammonia plant from hydrocarbons and air is feasible to be established with the profits that the plant gets after tax is Rp. 867,865,241,024/year and the plant's Payback Period (PBP) is 1.8 years. Keywords: Ammonia, Economic Analysis, Natural Gas, Hydrocarbon, Plant Design